The VEGFs/VEGFRs system in Alzheimer’s and Parkinson’s diseases: Pathophysiological roles and therapeutic implications - Claudia Ceci; Pedro Miguel Lacal; Maria Luisa Barbaccia; Nicola Biagio Mercuri; Grazia Graziani; Ada Ledonne (Pharmacological Research, 2024)
The vascular endothelial growth factors (VEGFs) and their cognate receptors (VEGFRs), besides their well-known involvement in physiological angiogenesis/lymphangiogenesis and in diseases associated to pathological vessel formation, play multifaceted functions in the central nervous system (CNS). In addition to shaping brain development, by controlling cerebral vasculogenesis and regulating neurogenesis as well as astrocyte differentiation, the VEGFs/VEGFRs axis exerts essential functions in the adult brain both in physiological and pathological contexts. In this article, after describing the physiological VEGFs/VEGFRs functions in the CNS, we focus on the VEGFs/VEGFRs involvement in neurodegenerative diseases by reviewing the current literature on the rather complex VEGFs/VEGFRs contribution to the pathogenic mechanisms of Alzheimer’s (AD) and Parkinson’s (PD) diseases. Thereafter, based on the outcome of VEGFs/VEGFRs targeting in animal models of AD and PD, we discuss the factual relevance of pharmacological VEGFs/VEGFRs modulation as a novel and potential disease-modifying approach for these neurodegenerative pathologies. Specific VEGFRs targeting, aimed at selective VEGFR-1 inhibition, while preserving VEGFR-2 signal transduction, appears as a promising strategy to hit the molecular mechanisms underlying AD pathology. Moreover, therapeutic VEGFs-based approaches can be proposed for PD treatment, with the aim of fine-tuning their brain levels to amplify neurotrophic/neuroprotective effects while limiting an excessive impact on vascular permeability.